Construire des politiques alimentaires urbaines - Brand, Caroline; Bricas, Nicolas; Conaré, Damien; Daviron, Benoit; Debru, Julie; Michel, Laura; Soulard, Christophe-Toussaint (éditions Quae, 2017)
This book describes the existing conceptual frameworks for an analysis of urban food policies at the crossroads of food system and sustainable city concepts. It serves as a basis to identify research issues in relation to local city government initiatives in the North and South.